Potensi Pestisida Nabati Kombinasi Ekstrak Daun Lamtoro (Leucaena leucocephala) dan Biji Mahoni (Swietenia macrophylla King) Guna Menekan Hama Pada Tanaman Cabai Rawit (Capsicum frutescens L.) - Dinaisa Eriyanti; Sonja Verra Tinneke Lumowa; Herliani Herliani; Masitah Masitah (Symbiotic: Journal of Biological Education and Science, 2024)
One economically valuable horticultural vegetable crop is cayenne peppers (Capsicum frutescens L.). Because plant pests contribute to the reduction in cayenne pepper production, this study aims to determine whether the leaves of the Leucaena leucocephala and the seeds of the Swietenia macrophylla King can be used as botanical pesticides to control pests that attack cayenne pepper plants. An innovative experimental approach was applied in this study. This study utilized a Randomized Block Design (RAK) with 125 plants, which included 5 treatments, 5 replications, and 5 groups. We shall undertake this research for a duration of three months. The research was conducted in the yard of the researcher's house in Long Iram City, West Kutai Regency, East Kalimantan. The purpose of the study was to determine the effectiveness of a botanical pesticide on Cayenne Pepper plants. The researchers found that a combination of Lamtoro Leaf extract (Leucaena_Leucocephala) and mahogany seeds (Swietenia macrophylla King) reduced the intensity of insect pest attacks. The T4 treatment, which contained 70% of the extracts, was the most effective botanical pesticide for the plants.